Task Based Approach: An Approach to Develop Writing Skills in English of Engineering Students Leads to Effective Communication Skills - Kadam, Dipali M.; Pusawale, Swati N. (Journal of Engineering Education Transformations, 2025)
21st century students are expecting an educational system that works for and with them. The teaching-learning process is shifted from teachercentered to student-centered through innovative teaching-learning techniques. With the advancement of technology and globalization, communication skills in English language, as a life-long learning skill is an essential component in engineering education as an employability skill. Communication is one of 11 key outcomes designed by Accreditation Board for Engineering and Technology (ABET). Listening, speaking, reading, and writing (LSRW) are considered as four basic language skills, contributed major role in developing communication skills in English language. Though all skills are equally important, writing is the stepping stone in verbal communication yet difficult to acquire without knowledge or mastery on the remaining three skills. Currently teaching-learning process is shifted from chalk and talk to the implementation of various approaches based on cooperative and collaborative learning and integration of Information and Communication Technology in English Proficiency class. Some effective approaches are computer assisted language learning, mobile assisted language learning, technology enabled language learning, project based, problem based & puzzle-based language learning, flipped classroom based language learning, and task based language learning. The present paper aims to study the effective implementation of Task based approach in English language classroom to develop writing skills of F. Y. B. Tech students with other 21st century life skills by implementing various tasks-based activities as per need analysis of learners in order to ensure their active participation. Total 50 students were enrolled as an experimental group. The impact of selected approach was evaluated using quantitative and qualitative methodologies. The quantitative assessment was based on rating method whereas the qualitative was based on rubrics. The findings revealed that there is significant improvement not only in the writing skills of experimental group students but also listening, speaking, and reading skills, leading to effective communication skills in English Language.